Assessment of Fluid Status in Dialysis: Clinical Importance and Diagnostic Tools - Juliana Damas; Vasco Fernandes (Publicações Ciência e Vida, 2022)
Fluid status is crucial for dialysis patients. Volume overload is a major cardiovascular risk factor. Nevertheless, volume depletion is associated with myocardial stunning and cerebral ischaemia. For decades, many diagnostic tools have been proposed for increased accuracy in evaluation of volemia, considering that clinical assessment is unreliable. Lung ultrasound and bioimpedance analysis emerged as the most useful tools, although randomized clinical studies are lacking to implement their universal use. Early management of hydration may improve clinical outcomes, as it allows personalized dialysis prescriptions and nutritional support.